2007
DOI: 10.1097/ede.0b013e318068646a
|View full text |Cite
|
Sign up to set email alerts
|

Health Consequences of the Increasing Caesarean Section Rates

Abstract: Caesarean section (C-section) rates are rising in many middle- and high-income countries, with the justification that higher rates of C-section are associated with better outcomes. A review of 79 studies comparing outcomes of elective caesarean sections with vaginal deliveries, including both observational studies and randomized trials, suggests that caesarean sections may have substantially greater risks than vaginal deliveries. In this issue of Epidemiology, Leung and colleagues present data from Hong Kong o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
114
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(116 citation statements)
references
References 10 publications
0
114
0
2
Order By: Relevance
“…Several studies have shown an association between CS rate and maternal and infant mortality at population level in low income countries where large sectors of the population lack access to basic obstetric care [7,8,10]. The CS rate above a certain limit have not shown additional benefit for the mother or the baby, and some studies have even shown that high CS rates could be linked to negative consequences in maternal and child health [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown an association between CS rate and maternal and infant mortality at population level in low income countries where large sectors of the population lack access to basic obstetric care [7,8,10]. The CS rate above a certain limit have not shown additional benefit for the mother or the baby, and some studies have even shown that high CS rates could be linked to negative consequences in maternal and child health [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A similar rate was observed in the full-term infant population. This number is far greater than recommended by the World Health Organization (15%) 3 and is not explained alone by the described medical indications for CS. Elective CS played an important role in the high rates observed and require further evaluation to determine what percent were the result of previous non-medical indications.…”
mentioning
confidence: 60%
“…Practices fitting this description include routine episiotomy incisions, injudicious use of oxytocics, overuse of cesarean sections and artificial rupture of membranes (AROM) [29]. Unnecessary use of episiotomy incisions and cesarean sections and their associated risks to mothers and babies have frequently been noted in the literature [30,31]. In our study, one in every three women had an episiotomy incision, which included women with previous births.…”
Section: Discussionmentioning
confidence: 97%
“…AROM is generally recommended when there is fetal distress or some maternal indication so that the delivery process can be expedited [30,32]. We did not collect information on the indications for AROM for this study, but we believe that the high rate of this practice suggests unnecessary intervention.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation